Developmental and professional activities of elite badminton players - Ford, P. R.; Broadbent, D. P.; Low, J.; Alder, D.; Causer, J. (World Badminton Federation, 2016)
The activities that athletes participate in during their development contribute significantly to skill acquisition and the attainment of expert performance (for examples, see Baker, Côté, & Abernethy, 2003; Ford et al., 2012; Law, Côté, & Ericsson, 2007;). To date, no research has been conducted examining the developmental activities of expert athletes in racket sports, including badminton. The aim of this research is to examine the amount and types of developmental and professional activities engaged in by elite badminton players in Europe and Malaysia.